Recent Trends of Infectious Complications Following Heart Transplantation. Issue 10 (October 2020) - Multani, Ashrit; Moayedi, Yasbanoo; Puing, Alfredo; Henricksen, Erik; Garvert, Donn W.; Gomez, Carlos A.; Tremblay-Gravel, Maxime; Bunce, Paul E.; Luikart, Helen; Ross, Heather J.; Khush, Kiran K.; Montoya, Jose G.; et al.
Abstract : Background: Heart transplantation is a life-saving procedure that has seen improvements in transplant and patient outcomes due to advances in immunosuppression and prevention of posttransplantation infectious episodes (IEps). This study systematically evaluates IEps in the modern era of heart transplantation at Stanford University Medical Center. Methods: This is a single-center retrospective review that includes 279 consecutive adult heart transplantation recipients from January 2008 to September 2017. Baseline demographic, clinical, serological, and outcomes information were collected. Kaplan-Meier estimator was used to assess survival stratified by IEp occurrence within the first year. Results: A total of 600 IEps occurred in 279 patients (2.15 IEps per patient) during a median follow-up period of 3 years. Overall survival was 83.3% (95% confidence interval [CI], 76.2-88.4) at 1 year posttransplantation for those with any IEp compared with 93.0% (95% CI, 87.2-96.4) in those without IEp ( P = 0.07). Bacterial IEps were the most common (n = 375; 62.5%), followed by viral (n = 180; 30.0%), fungal (n = 40; 6.7%), and parasitic (n = 5; 0.8%). IEps by Gram-negative bacteria (n = 210) outnumbered those by Gram-positive bacteria (n = 142). Compared with prior studies from our center, there was a decreased proportion of viral (including cytomegalovirus), fungal (including Aspergillus spp. and non- Aspergillus spp. molds), and Nocardia infections. There were no IEps due to Mycobacterium tuberculosis, Pneumocystis jirovecii, or Toxoplasma gondii . Conclusions: A significant reduction in viral, fungal, and Nocardia IEps after heart transplantation was observed, most likely due to advancements in immunosuppression and preventive strategies, including pretransplant infectious diseases screening and antimicrobial prophylaxis.